2023
DOI: 10.1186/s13034-022-00554-y
|View full text |Cite
|
Sign up to set email alerts
|

Conspiracy beliefs and COVID-19 guideline adherence in adolescent psychiatric outpatients: the predictive role of adverse childhood experiences

Abstract: Background Conspiracy beliefs have become widespread throughout the COVID-19 pandemic. Previous studies have shown that endorsing conspiracy beliefs leads to lower protective guideline adherence (i.e., wearing face masks), posing a threat to public health measures. The current study expands this research across the lifespan, i.e., in a sample of adolescents with mental health problems. Here, we investigated the association between conspiracy beliefs and guideline adherence while also exploring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 68 publications
0
0
0
Order By: Relevance
“…Additionally, a small fee was paid for participation and may have led to over‐representation of individuals suffering monetary disadvantage. One study (Goreis et al, 2023) took a sample from psychiatric outpatients to examine conspiracy theories in adolescents with mental health diagnoses. The authors reported that the sample represented approximately 10% of all outpatients within the department and, as such, might not be representative of all adolescents engaged with the outpatient department.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Additionally, a small fee was paid for participation and may have led to over‐representation of individuals suffering monetary disadvantage. One study (Goreis et al, 2023) took a sample from psychiatric outpatients to examine conspiracy theories in adolescents with mental health diagnoses. The authors reported that the sample represented approximately 10% of all outpatients within the department and, as such, might not be representative of all adolescents engaged with the outpatient department.…”
Section: Resultsmentioning
confidence: 99%
“…The included study of adolescent psychiatric outpatients by Goreis et al (2023) reported lower beliefs among adolescents compared with adults in relation to reported generic conspiracy theory beliefs in studies using the same measure. However, the sample age range began at 11 years; given that the current review has reported key stage 4 high school students (11–14 years) as having lower conspiracy theory beliefs, it would be expected that the overall score for the adolescent sample used by Goreis et al would be lower than adult samples.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations